New conceptual approaches to students' independent work organization - Коновал, Олександр Андрійович; Туркот, Тетяна Іванівна (Pedagogy of Higher and Secondary Education, 2013)
Konoval O. A., Turkot T. I. New conceptual approaches to students' independent work organization. The article is devoted to the analysis of the content of the theoretical and methodological (systemic, axiological, synergetic) approaches to the organization of students’ independent work. The necessity of their realization in the modern educational and informational environment of higher educational establishment has been substantiated.